VIEW OF ROLE OF MEN IN BOBO MAGAZINE’S - Errika Dwi Setya Watie; Kharisma Ayu Febriana; Firdaus Azwar Ersyad (Universitas Kristen Satya Wacana, 2018)
The purpose of the research related to the description of the role of men in Bobo magazine is to find out how the representation of men in Bobo magazine, more specifically to find out the content in children's magazines that portray an ideal gender role according to the role of balance in the spirit of emancipation. The research uses qualitative methods with descriptive interactive analysis techniques in which this study emphasizes discursive material and conversion into discursive material from non-discursive material. In this study also found that Bobo magazine as a children's magazine featured a lot of men who were bound by patriarchal culture. Patriarchal culture is very dominant in Bobo magazine for readers or the public. Thus, Bobo magazine shows the truth that patriarchal ideology is very dominant